"I Could Do Stereotypical Old People Things … but I Feel Like I Would Get Bored With That Stuff": College Students' Proactive Steps to Avoid Negative Aspects of Aging. (July 2021) - Hahn, Sarah J.; Kinney, Jennifer M.
The preventive and corrective proactivity model explores how internal and external resources mediate age-related stressors to counter negative outcomes of aging. Older adults' proactivity about their future is consistently associated with higher quality of life, but research has not explored younger adults' perceptions of their aging. We used interpretive phenomenology analysis to analyze 24 students' essays from the beginning and end of an introductory gerontology course to understand anticipated adaptation to their 75-year-old self. The superordinate theme proactive steps to avoid negative aspects of aging comprised five subordinate themes (being productive, exercising and eating right, being financially stable, being socially connected, and the roles of older adults). Students presented unrealistically positive selves at 75 and discussed how to maintain and adapt to redefine their aging experience. Findings have implications for research on adaption, proactivity, and the future-self, and suggest that pedagogy incorporates realistic expectations of aging.